2021
DOI: 10.1093/jhps/hnab014
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and complications of patients undergoing Salter’s innominate osteotomies for hip dysplasia: a systematic review of comparative studies

Abstract: The purpose of this systematic review is to assess outcomes and complications of patients undergoing Salter’s innominate osteotomies (SIOs) for the correction of hip dysplasia along with patient and technical factors that can be optimized to improve outcomes after SIO. MEDLINE and EMBASE were searched from data inception to 9 October 2018. Data were presented descriptively. Twenty-seven studies were identified including 1818 hips (87.1%) treated with SIO (mean age of 2.1 ± 2.5 years and mean follow-up of 3.5 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The prevalence of AVN in the 4 -8 years group ranges between 3% and 60% (8). In a systemic review of comparative studies, they reported that the complication rate for Salter innominate osteotomy was 9.4% and AVN was the most common complication (23) (27). In our study, AVN of the femoral head was observed in two patients; according to Bucholz and Ogden's classification, one was Type 1 and one was Type 3 AVN.…”
Section: Discussionsupporting
confidence: 49%
“…The prevalence of AVN in the 4 -8 years group ranges between 3% and 60% (8). In a systemic review of comparative studies, they reported that the complication rate for Salter innominate osteotomy was 9.4% and AVN was the most common complication (23) (27). In our study, AVN of the femoral head was observed in two patients; according to Bucholz and Ogden's classification, one was Type 1 and one was Type 3 AVN.…”
Section: Discussionsupporting
confidence: 49%
“…Although satisfactory results can be achieved in most patients after closed reduction and cast immobilization, some patients still develop residual acetabular dysplasia (RAD), which often requires a second surgical treatment [4][5][6][7]. Generally, a pelvic osteotomy according to Salter [8] or Pemberton [9], or a triple pelvic osteotomy [10], is recommended in patients with RAD following closed reduction and spica cast immobilization. Chaker et al and Faciszewski et al have reported good outcomes of pelvic osteotomy in patients with RAD following closed reduction and spica cast immobilization [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The acetabulum gains greater coverage of the femoral head and a larger weight-bearing area by osteotomy of the ilium and rotational movement of the distal fragment anterolaterally in SIO. Therefore, many surgeons believe that SIO has a limited corrective effect in older patients because of the decreased flexibility of the symphysis pubis and pelvic bones and the decreased ability of bone remodeling 9,10. Consequently, in older children, rotational osteotomies such as triple osteotomy and periacetabular osteotomy are preferred, but these are more invasive and the techniques are more difficult.…”
mentioning
confidence: 99%
“…Therefore, many surgeons believe that SIO has a limited corrective effect in older patients because of the decreased flexibility of the symphysis pubis and pelvic bones and the decreased ability of bone remodeling. 9,10 Consequently, in older children, rotational osteotomies such as triple osteotomy and periacetabular osteotomy are preferred, but these are more invasive and the techniques are more difficult. Furthermore, complications such as bleeding, failure of bony union, and loss of fixation are more frequent.…”
mentioning
confidence: 99%